Probing the Binding Pocket of the Broadly Tuned Human Bitter Taste Receptor TAS2R14 by Chemical Modification of Cognate Agonists. (17th February 2016) - Karaman, Rafik; Nowak, Stefanie; Di Pizio, Antonella; Kitaneh, Hothaifa; Abu‐Jaish, Alaa; Meyerhof, Wolfgang; Niv, Masha Y.; Behrens, Maik
Abstract : Sensing potentially harmful bitter substances in the oral cavity is achieved by a group of ˜ 25 receptors, named TAS2Rs, which are expressed in specialized sensory cells and recognize individual but overlapping sets of bitter compounds. The receptors differ in their tuning breadths ranging from narrowly to broadly tuned receptors. One of the most broadly tuned human bitter taste receptors is the TAS2R14 recognizing an enormous variety of chemically diverse synthetic and natural bitter compounds, including numerous medicinal drugs. This suggests that this receptor possesses a large readily accessible ligand binding pocket. To allow probing the accessibility and size of the ligand binding pocket, we chemically modified cognate agonists and tested receptor responses in functional assays. The addition of large functional groups to agonists was usually possible without abolishing agonistic activity. The newly synthesized agonist derivatives were modeled in the binding site of the receptor, providing comparison to the mother substances and rationalization of the in vitro activities of this series of compounds. Abstract : To assess size and accessibility of the ligand binding pocket of the human bitter taste receptor TAS2R14, cognate agonists including medicinal drugs were chemically modified (1). The derivatives and mother substances were subjected to functional calcium imaging experiments (2) and computational studies (3) revealing which ligand features are tolerated within the TAS2R14 binding pocket.